-

-

 

 

 

 

 

 

 

 

 

 

 

 

 

-

 

 

 

 

 

 

 

 

 

 

 

 

 

: 4 5

..

 

:

..

 

 

 

1998.

 

 

-

- - - - - - - - - - - - - - - - - - - 3

ࠠ - - - - - - - - - - - - - - - - - - - - - - 5

䠠 - - - - - - - - - - - - - - - - - - - - - - 8


- - - - - - - - - - - - - - - - - - - - - - 10

頠 - - - - - - - - - - - - - - - - - - - - - - 13

젠 - - - - - - - - - - - - - - - - - - - - - - 16


Š - - - - - - - - - - - - - - - - - - -

- - - - - - - - - - - - - - - - - - -





















-

 

 

 

 

j(x,y) - , . (DEF) :


d2j + d2j = 0

dx2 dy2

( ABGH) - :

d2j + d2j = 0

dx2 dy2

q - e;

enn - ;

Nd(x,y) - ;

Na(x,y) - ;

e0 -






0 D E

y



B G

C F


A H


x

.1.

 
 




:

 

j| BC = Uu

j| DE = U

j| FG = Uc

j| AH = Un

 

AB GH:


dj = 0 dj = 0

dy AB dy GH

OY

:


dj = 0 dj = 0

dy DC dy EF


-

:


j| -0 = j| +0

eok Ex |-0 - enn Ex |+0 = - Qss

 

Qss - ;

eok - ;

enn - .

+0 -0 CF . - .










 

 








  {(x,y) : 0 < x < Lx , 0 < y < Ly }


W={(x,y) : 0 < i < M1 , 0 < j < M2}

x0 =0 , y0=0, xM1 = Lx , yM2 = Ly

xi+1 = xi + hi+1 , yj+1 = yj+ rj+1

i = 0,...,M1-1 j = 0,...,M2-1

 





























:

xi+ ½ = xi + hi+1 , i = 0,1,...,M1-1

2

yj+ ½ = yj + rj+1 , j = 0,1,...,M2-1

2

:

U(xi,yj) = Uij

I(xi+½,yj) = Ii+½,j

I(xi,yj+½) = Ii,j+½

 

:


Dj = - q (Nd + Na)

e0en

 

Q(x,y)

:

Vij = { (x,y) : xi- ½ < x < xi+ ½ , yj- ½ < y < yj+ ½ }

 

xi+ ½ yj+ ½ xi+ ½ yj+ ½

ò ò Dj dxdy = ò ò Q(x,y)dxdy

xi- ½ yj- ½ xi- ½ yj- ½

:

yj+½ xi+½

ò(Ex(xi+½,y) - Ex(xi-½,y) )dx + ò(Ey(x,yj+½) - Ey(x,yj-½))dy=

yj-½ xi-½

 

xi+ ½ yj+ ½

= ò ò Q(x,y)dxdy

xi-   ½ yj- ½

:

Ex(x,y) = - dj(x,y)

dx (*)

Ey(x,y) = - dj(x,y)

dy

x - .

 


yj-½ < y < yj- ½ Ex(xi + ½,yj) = Ei+ ½ ,j = const

yj-½ < y < yj- ½ Ex(xi - ½ ,yj) = Ei- ½ ,j = const (**)

xi-½ < x < xi+ ½ Ey(xi, yj + ½) = Ei,j+ ½ = const

xi-½ < x < xi+ ½ Ey(xi, yj ) = Ei,j - ½ = const

xi- ½ < x < xi+ ½

yj- ½ < y < yj+ ½ - Q(x,y) = Qij = const


 


(Ex)i+ ½ ,j - (Ex)i -½ ,j r*j + (Ey)ij+ ½ - (Ey)ij- ½ h*i = Qijh*i r*j

h*i = hi - hi+1 , r*j = rj - rj+1

2 2

i+ ½ ,j j(x,y) :

xi+1

òEx(x,yj)dx = - ji+1,j - jij

xi

(**) y=yj:


(Ex)i+ ½ ,j = - ji+1j - jij

hi+1

:

(Ey)i,j+ ½= - jij+1 - jij

rj+1


:

 


(Dj)ij = 1 j i+1,j - j ij - j i j - j i-1,j + 1 j i j+1 - j ij - j ij - j ij-1 =

h*i hi+1 hi r*j rj+1 rj


= Ndij + Naij





















 


SiO2

e1









Si y

en








x





V0j

yj+ ½ x ½

ene0 ò(Ex(x ½ ,y) - E+x(0,y))dy + ene0 ò (Ey(x,yj+ ½) - Ey(x,j- ½ ))dx =

yj- ½ 0

x ½ yj+½

= q ò ò (Nd + Na)dxdy

0 yj-½

V`0j

: 1, 2






           

2009 .